Simulataneous Quantitation of Gallic Acid from Fruits of Phyllanthus emblica Linn., Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. - SHARMA, AMBIKA; SHAILAJAN, SUNITA (Asian Journal of Chemistry, 2010)
Fruits of Phyllanthus emblica Linn., Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. are commonly used as herbal raw materials in many Ayurvedic and herbal formulations. These fruits are either used individually or in combination known as 'Triphala'. Fruits of Phyllanthus emblica Linn., Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. have been reported to contain gallic acid. Gallic acid is a widely occurring phenolic compound of plant origin. Gallic acid is selected as a bioactive marker due to its easy availability, common presence in these fruits and as antiobesity property. Recently, the concept of marker-based standardization of herbal drugs is gaining momentum. A simple, sensitive and reliable high performance thin layer chromatographic method has been established for simultaneous quantification of gallic acid from fruits of Phyllanthus emblica Linn., Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. Gallic acid separation was achieved from Phyllanthus emblica Linn., Terminalia bellirica (Gaertn.) Roxb. and Terminalia chebula Retz. of different geographical regions of India and Nepal in a common mobile phase toluene:ethyl acetate:formic acid, 2:7:1 (v/v). After development, detection and quantitation of plates were performed by densitometry at 275 nm. The response to gallic acid in all the three fruits extracts was a linear function of concentration over the range 20 to 100 μg mL-1. There was significant variation in gallic acid content of fruit collected from different regions. Gallic acid was maximum in Phyllanthus emblica Linn. collected from Dehradun (0.721 %), in Terminalia bellirica (Gaertn.) Roxb. collected from Maharastra (Karjat) (0.561 %) and Terminalia chebula Retz. collected from Madhya Pradesh (0.905 %).